Synthesis and characterization of cyclotriphosphazene derivatives bearing azole groups. (15th October 2016) - Uslu, Aylin; Özcan, Elif; Dural, Sevilay; Yuksel, Fatma
Graphical abstract: New cyclotriphosphazene derivatives containing azole side groups and morpholino or propandioxy moieties as cosubstituent groups have been designed and synthesized. They have been investigated from the point of view of Lipinski rule of five, drug-likeness, toxicity profiles and other physicochemical properties using online calculation toolkits. Abstract: A series of new cyclophosphazene derivatives were obtained from the reactions of morpholino or propandioxy derivatives of cyclotriphosphazenes with imidazole, benzimidazole and pyrazole. Reported compounds [N3 P3 Cl5 (NC4 H8 O)] (1 ), cis -[N3 P3 Cl4 (NC4 H8 O)2 ] (2 ), trans -[N3 P3 Cl4 (NC4 H8 O)2 ] (3 ), trans -[N3 P3 (NC4 H8 O)2 (R)4 ] [R = imidazole (4 ); benzimidazole (5 ); pyrazole (6 )], spiro-[N3 P3 (OC3 H6 O)(R)4 ] [R = imidazole (8 ); benzimidazole (9 ); pyrazole (10 )] were characterized using spectroscopic methods, elemental analysis and X-ray crystallography. Stereogenic properties of compounds having chiral centers were discussed. The physicochemical parameters and the toxicity risk assessment of the synthesized compounds were estimated using Molinspiration and Osiris property calculation methods.